Famine crimes politics & the disaster relief industry in Africa - De Waal, Alexander (London Indiana University Press, 1997)
"This is unquestionably an important book by a writer whose accomplishments as a researcher, critic and activist on famine and on human rights in Africa are widely respect." ?International Affairs
Includes bibliographical references (p. 222-232) and index.
Keywords: Food relief--Government policy--Africa.